Mukhamandapa (front porch) with ornate pillars - Temples of India Project Team (Jio Institute, 2024)
The west-facing entrance of the temple has a mukhamandapa (front porch) with ornate pillars. Octagonal in section, the pillars have circular rings of intricate designs on the shaft, and the base is decorated with sculptures. The pillars are made of a different stone than the main temple.